2011
DOI: 10.1002/dvdy.22695
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic zebrafish model of targeted oocyte ablation and de novo oogenesis

Abstract: We describe here a novel transgenic zebrafish, Tg(zpc:G4VP16/UAS:nfsB-mCherry) that effectively demonstrates the targeted oocyte ablation in the adult zebrafish ovary. This transgenic line expresses bacterial nitroreductase enzyme (nfsB) under the control of the oocyte-specific zona pellucida C (zpc) gene promoter. Adult transgenic females exposed to the prodrug metronidazole demonstrated near-complete ablation of growing oocytes, resulting in ovarian degeneration and complete cessation of reproductive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…The appearance of aberrant cortical granules in zar1 oocytes at 33 dpf is the initial sign of defective oogenesis, but the mutant oocytes could last more than 2 weeks before they were cleared out, suggesting that detrimental factors accumulate gradually in the oocytes. Several studies support the hypothesis that oocytes are essential for ovarian development and may suppress testis development (Dranow et al, 2016(Dranow et al, , 2013Hartung et al, 2014;Houwing et al, 2008;Rodríguez-Marí et al, 2010Shive et al, 2010;White et al, 2011). We hypothesize that gradual loss of oocytes leads to testis development in zar1 homozygous females and eventually causes female-to-male sex reversal.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The appearance of aberrant cortical granules in zar1 oocytes at 33 dpf is the initial sign of defective oogenesis, but the mutant oocytes could last more than 2 weeks before they were cleared out, suggesting that detrimental factors accumulate gradually in the oocytes. Several studies support the hypothesis that oocytes are essential for ovarian development and may suppress testis development (Dranow et al, 2016(Dranow et al, , 2013Hartung et al, 2014;Houwing et al, 2008;Rodríguez-Marí et al, 2010Shive et al, 2010;White et al, 2011). We hypothesize that gradual loss of oocytes leads to testis development in zar1 homozygous females and eventually causes female-to-male sex reversal.…”
Section: Discussionsupporting
confidence: 78%
“…Zebrafish without germ cells develop into male adults, indicating germ cells are essential for female development (Campbell et al, 2015;Draper et al, 2007;Houwing et al, 2007;Siegfried and Nüsslein-Volhard, 2008;Slanchev et al, 2005). When oocytes are depleted in juveniles, zebrafish also develop into males (Dranow et al, 2013;Hartung et al, 2014;Houwing et al, 2008;Rodríguez-Marí et al, 2010Shive et al, 2010;White et al, 2011). Attenuation of apoptosis pathways by p53 deficiency restores ovarian development in otherwise all male fancl and brca2 mutants (Rodríguez-Marí et al, 2010Shive et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…21 Treatment in 10 mM MTZ for 24 h was used in the initial reports, 9,13 and has become a standard regimen for NTR-mediated ablation of multiple cell types. 2,[9][10][11][12][13]15,22,23 However, 24 h/10 mM MTZ treatments are problematic. For instance, nonspecific apoptosis within the superficial telencephalon has been noted.…”
Section: Introductionmentioning
confidence: 99%
“…1 To date, this system has been deployed in several different cell and tissue types in both larval and adult zebrafish. [9][10][11][12][13][14][15][16][17][18] Importantly, prodrugs are easily administered in aqueous media; thus, cell ablation can be induced in thousands of fish simultaneously, facilitating large-scale screens. 19 Accordingly, we recently developed a true high-throughput screening (HTS) methodology for identifying factors that regulate regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, it has been generally believed that the ovaries of mammals do not possess renewable stem cells but instead contain a finite reserve of oocytes that diminishes through postnatal life. Although the existence of ovarian germline stem cells (GSCs) has been obviously demonstrated and fully accepted for adult females of non-mammalian species [3][4][5] and for adult males of a majority of species [6] , the existence of ovarian GSCs in adult female mammals is still a subject of intense debate. In 2004, Johnson et al [1] demonstrated the existence of proliferative GSCs in the ovaries of adult mice, and recently, ovarian GSCs have been isolated and characterized in the ovaries of postnatal mice and reproductive-age women [7] .…”
Section: Introductionmentioning
confidence: 99%